Who runs the show in digitalized manufacturing? Data, digital platforms and the restructuring of global value chains. (25th March 2022) - Butollo, Florian; Schneidemesser, Lea
Abstract: This article explores the position of industrial Internet platforms (IIPs) in manufacturing value chains. We develop an understanding of the role of data in global value chains (GVCs), referring to literature on intangible assets and theories on platform business models. We use data from a qualitative empirical study based on 33 interviews on platforms active on the German market to answer (1) whether there are tendencies of oligopolization that lead to an accumulation of power on the side of the platforms, and (2) whether it is the platforms that capture most of the gains derived from higher productivity or lower transaction costs. The analysis shows that platforms mainly act as service providers and/or intermediaries that support manufacturing companies in reaping benefits from data. While the relationship between platforms and manufacturers currently corresponds to a symbiosis, a stronger power imbalance could evolve in the future since processes of oligopolization are likely.